Emerging markets in the post-liberalization period: Evidence from the raw milk market in rural Kenya - Kijima, Y.; Yamano, T.; Baltenweck, Isabelle (Springer, 2011)
This chapter examines how the raw milk market in western and central Kenya has developed after the dairy sector liberalization in 1992 by using panel data of 862 rural households. From the late 1990s to 2004, the proportion of households that sold milk to traders more than doubled, while it declined from 29% to 12% for those who sold milk to dairy cooperatives. To examine this change in the milk market, we use the price differentials between the farm gate and retail prices as a proxy for the functioning of the market. Our empirical analyses clearly show that the functioning of the market improved between the late 1990s and 2004.